Patient Safety and Organisational Accountability: Reassessing Criminal Liability Frameworks in Healthcare - Sarah Bennett; Amel Alghrani (The Modern Law Review, 2026)
Serious harm in healthcare often results from systemic failures, yet criminal accountability remains largely addressed through homicide law, gross negligence manslaughter and health‐and‐safety offences, frameworks that emphasise individual culpability and are ill‐suited to addressing organisational failings. The Corporate Manslaughter and Corporate Homicide Act 2007 was intended to redress this imbalance by prosecuting organisations for management failures causing death, yet its impact in healthcare remains limited: no NHS Trust has been convicted under this legislation. Persistent barriers, including proving an organisational ‘gross breach’, establishing causation across care systems and satisfying the senior‐management requirement, have constrained its use. While cases such as Lucy Letby have sharpened public attention on professional wrongdoing and organisational oversight, the practical and normative questions raised by system‐caused harm remain distinct. The Thirlwall Inquiry report provides an opportunity to reconsider whether the current legal architecture adequately addresses organisational responsibility. This article argues that although the Corporate Manslaughter and Corporate Homicide Act 2007 retains symbolic value, its practical limitations undermine its effectiveness in healthcare. It proposes reforms, including clarification of the senior‐management requirement, closer integration of corporate liability with patient‐safety governance mechanisms and enhanced use of remedial and publicity orders, to strengthen organisational accountability while preserving conditions for safe care.